STUDI ENVIRONMENTAL KUZNETS CURVE DI ASIA: SEBELUM DAN SETELAH MILLENNIUM DEVELOPMENT GOALS - Sri Indah Nikensari; Sekar Destilawati; Siti Nurjanah (Jurnal Ekonomi dan Pembangunan, 2025)
The environmental pollution can reduce subjective well-being.Thus study aims to prove the validity of the Environmental Kuznets Curve (EKC) hypothesis in high and middle income countries in Asia, also to analyze the differences in the effect of GDP per capita, energy consumption, and population on CO2 emissions in the same region before and after the MDGs. Data obtained from the World Bank for the period 1987-2014, where the analysis uses quantitative methods and expose facto, and through panel data regression equations to achieve research objectives. The results show that until 2014 the EKC hypothesis in the form of U-reversal has not occurred in the high income countries studied, but will occur when GDP per capita has reached USD 51.44 thousand. Whereas in the lower middle income countries, the pattern of the relationship between GDP per capita and CO2 emissions still forms a U curve, or in other words the ECC hypothesis will not occur in these countries, because in some countries it is still in the early stages of development. The results also showed that prior to the MDGs (2000), GDP per capita, energy consumption and population in high income countries contributed to the increase in CO2 emissions, but after the MDGs, rising GDP per capita was able to reduce CO2 emissions. Whereas in low middle income countries, at the beginning of the study before the MDGs, the data showed that CO2 was already high at a time when GDP per capita was still low, and after MDGs, increases in GDP per capita still contributed to rising CO2 emissions.